DEVELOPMENT AND CHARACTERIZATION OF FOLIC ACID MICROPARTICLES FORMED BY SPRAY-DRYING WITH GUM ARABIC AND MALTODEXTRIN - LOPERA C., Seneida M.; GUZMÁN O., Cielo; CATAÑO R., Carlos; GALLARDO C., Cecilia (Vitae, 2009)
The folic acid is an essential vitamin, it is involved in the essential aminoacids biosynthesis and some process associated to DNA. Folic acid undergoes degradation reactions when is exposed to light, acid or alkaline medium and oxygen atmosphere. For this reason it is necessary to develop strategies to improve its stability not affecting its biological activity. In this connection the obtaining of microparticles by spray drying, using arabic gum and maltodextrin blends is proposed. The microparticles could act as a carrier of folic acid providing it protection. In this study, microparticles of folic acid were obtained using four different blends of arabic gum and maltodextrin. The particles size distribution, morphology, encapsulation efficiency and dissolution profile were assessed for the different types of microparticles. The results showed different aspects: the microparticles morphology changed with the ratio arabic gum – maltodextrine, the encapsulation efficiency was high for four types of studied microparticles, the particles size distribution did not change with the wall materials ratio, the dissolution profiles showed a limited dissolution percentage, and microparticles of arabic gum-maltodextrin 70-30 showed the best profile. The arabic gum favored the encapsulation of folic acid and when it is mixed with maltodextrin the morphology, encapsulation efficiency and dissolution improved. Probably there is an optimum ratio of two wall materials providing optimum properties to microparticles.